Reverse-phase protein microarrays: application to biomarker discovery and translational medicine. (September 2007) - VanMeter, Amy; Signore, Michele; Pierobon, Mariaelena; Espina, Virginia; Liotta, Lance A; Petricoin III, Emanuel F
Mapping of protein signaling networks within tumors can identify new targets for therapy and provide a means to stratify patients for individualized therapy. Kinases are important drug targets, as such kinase network information could become the basis for development of therapeutic strategies for improving treatment outcome. An urgent clinical goal is to identify functionally important molecular networks associated with subpopulations of patients that may not respond to conventional combination chemotherapy. Reverse-phase protein microarrays are a technology platform designed for quantitative, multiplexed analysis of specific phosphorylated, cleaved, or total (phosphorylated and nonphosphorylated) forms of cellular proteins from a limited amount of sample. This class of microarray can be used to interrogate cellular samples, serum or body fluids. This review focuses on the application of reverse-phase protein microarrays for translational research and therapeutic drug target discovery.